2015
DOI: 10.1007/s11938-014-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Drug Management in the Elderly IBD Patient

Abstract: Managing inflammatory bowel disease (IBD) in a world of immunomodulators and biologics is complex enough, but managing the elderly IBD patient is further confounded by multiple comorbidities, polypharmacy with drug-drug interactions, and cognitive mobility/motility disturbances. Social and insurance coverage issues also always lurk in the background. All of these factors summate into a daunting challenge for the clinician. In this review, we aim to describe important considerations when prescribing to an elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…24 Therefore, caution in drug prescription is warranted, in particular in the frail elderly population. [25][26][27] Data on the disease course of EO IBD are mainly derived from small selected referral center cohorts, some collected decades ago. [28][29][30][31][32][33][34][35][36][37][38][39] Recent population-based data from the Hungarian registry and the French EPIMAD registry suggested a somewhat milder course of IBD diagnosed at older age, yet the number of elderly patients was limited 40 or data from the corresponding adult population were lacking, 41 impeding a direct comparison.…”
mentioning
confidence: 99%
“…24 Therefore, caution in drug prescription is warranted, in particular in the frail elderly population. [25][26][27] Data on the disease course of EO IBD are mainly derived from small selected referral center cohorts, some collected decades ago. [28][29][30][31][32][33][34][35][36][37][38][39] Recent population-based data from the Hungarian registry and the French EPIMAD registry suggested a somewhat milder course of IBD diagnosed at older age, yet the number of elderly patients was limited 40 or data from the corresponding adult population were lacking, 41 impeding a direct comparison.…”
mentioning
confidence: 99%
“…Thiopurine (6‐mercaptopurine, azathioprine) has been proven to be effective and safe for maintaining remission in moderate to severe corticosteroid‐dependent disease in elderly UC patients, 12 , 34 , 35 and its efficacy has been reported in Asian countries. 36 …”
Section: Medical Therapy Of Elderly Ulcerative Colitismentioning
confidence: 99%
“…Of note, for the elderly population at risk for polypharmacy, 5-ASA has been shown to interact with Warfarin[28]. In addition, combining antacids and 5-ASA may hinder the therapeutic effects of 5-ASA[29].…”
Section: Medical Therapymentioning
confidence: 99%
“…Similarly to 5-ASA, there is insufficient evidence to suggest that the treatment efficacy of thiopurines in the older IBD population is different than that of the younger population. Still, studies have shown a low usage of thiopurines in the elderly population that is most likely driven by the higher risk of malignancy associated with this class of drugs[29,37]. Indeed, in their various prospective observational studies, the CESAME Study group has found that ongoing and previous exposure to thiopurines increase the risk of developing non-melanoma skin cancer, that previous exposure comes with a seven-fold increased risk of developing a myeloid disorder and that ongoing exposure increases the risk of urinary tract cancers[38-39].…”
Section: Medical Therapymentioning
confidence: 99%
See 1 more Smart Citation